Nocardiosis in a Kidney-Pancreas Transplant. (21st December 2009) - Fontana, I.; Gasloli, G.; Rossi, A. Magoni; Bornacina, C.; Dodi, F.; Bertocchi, M.; Soro, O.; Diviacco, P.; De Negri, A.; Bocci, E.; Ferrari, C.; Giannone, A.; et al.
Abstract : 34-year-old man with chronic renal and pancreas failure in complicated diabetic disease received a kidney-pancreas transplantation. On the 32nd postoperative day, an acute kidney rejection occurred and resolved with OKT3 therapy. The patient also presented refractory urinary infection by E. Fecalis and M. Morganii, and a focal bronchopneumonia in the right-basal lobe resolved with elective chemotherapy. During the 50th post-operative day, an intense soft tissue inflammation localized in the first left metatarsal-phalangeal articulation occurred (Figure 1) followed by an abscess with a cutaneous fistula and extension to the almost totality of foot area. The radiological exam revealed a small osteo-lacunar image localized in the proximal phalanx head of the first finger foot. From the cultural examination of the purulent material, N. Asteroides was identified. An amoxicillin-based treatment was started and continued for three months, with the complete resolution of infection This case is reported for its rarity in our casuistry, and for its difficult differential diagnosis with other potentially serious infections.